Numerical modeling of dilution and transport of highly mineralized brines in turbulent flows - Lyubimova, Tatyana Petrovna; Lepikhin, Anatoliy Pavlovich; Parshakova, Yanina Nikolaevna; Tiunov, Alexey Alexandrovich (Computational Continuum Mechanics, 2010)
A three-level scheme is suggested for the numerical simulation of transport and dilution of highly mineralized brines in water bodies. The first step involves the use of the one-dimensional hydrodynamic model based on the Sen-Venan equations, which covers the entire computational domain. The results obtained in the framework of the one-dimensional model are used to set boundary conditions for the second-level model based on the shallow water equations. Numerical data obtained in the framework of the two-dimensional model are sufficient if there is no significant density stratification at the initial dilution cross-section and if the depth-averaged characteristics are applicable to the problem conditions. In the opposite case, three-dimensional consideration is required. Three-dimensional modeling was carried out for the water body domain close to the surplus brine discharge. Two variants of the location of a discharge device are considered. It is found that in the case when the discharge device is located near the bottom, substantial non-uniformity of the pollutant distribution over the depth takes place. The location of the discharge device near the free surface results in much better dilution of brines and reduces the pollutant accumulation near the bottom. Thus, the results of three-dimensional calculations allow us to recommend the location of discharge devices for highly mineralized heavy brines near the free surface.